Cyberbullying among school going adolescents. What are the associated factors? - Olutola, Bukola; Whitehouse, Carmen (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: Bullying either face-to face or cyber bullying has been one of the problems experienced among adolescents. Cyber-bullying is a type of bullying that is done over the internet, and it is a new phenomenon because of the exposure of children to social media through the internet. To explore the factors associated with cyber-bullying, this study looked at cyber-bullying among the school going adolescents in Thailand in 2021. Methods and Materials: The study used the Thailand Global School-Based Student Health Survey 2021. Data analysis was conducted using both the descriptive analysis and multivariable logistic regression. Findings: Of the 5661 adolescents who participated in the study, 46.9% (2504) were males. Fifteen percent (n=790) of the respondents reported that they had ever been cyber-bullied in the past 12 months while 20% (n=1172) reported that they had ever been bullied on school property in the past 12 months. The prevalence of physical bullying (23.7% vs. 16.7%; p=0.001) and cyber-bullying (16.9% vs. 13.3%; p=0.014) was higher among male respondents than their female counterparts. Frequent feeling of loneliness, and suicide consideration were associated with cyber-bullying. Those who smoked cigarette between 1 and 9 days (AOR: 1.70; 95% Conf. Int: 1.29-2.24) and those who smoked between 10 and 30 days (AOR: 2.41; 95% Conf. Int: 1.47-3.93) in the past 30 days were more likely to have ever been cyber-bullied in the past 12 months compared to non-smokers. Conclusion: This study showed that suicide consideration, cigarette smoking, and loneliness were associated with cyber-bullying.